Interleukin-17–targeted treatment in patients with spondyloarthritis and associated cardiometabolic risk profile - Queiro, Rubén; Aurrecoechea, Elena; Alonso Castro, Sara; Villa Blanco, Ignacio; Brandy-Garcia, Anahy; Linge, Raquel (Frontiers in Immunology, 2023)
Spondyloarthritis is a group of immune-mediated rheumatic disorders that significantly impact patients’ physical function and quality of life. Patients with spondyloarthritis experience a greater prevalence of cardiometabolic disorders, such as obesity, hypertension, dyslipidemia and diabetes mellitus, and these comorbidities are associated with increased spondyloarthritis disease activity and risk of cardiovascular events. This narrative review summarizes the evidence for a physiological link between inflammatory status and cardiometabolic comorbidities in spondyloarthritis, as well as the impact of interleukin (IL)-17 blockade versus other molecular mechanisms in patients with cardiometabolic conditions. The IL-23/IL-17 axis plays a pivotal role in the pathophysiology of spondyloarthritis by promoting inflammation and tissue remodeling at the affected joints and entheses. The importance of the IL-23/IL-17 signaling cascade in underlying sub-clinical inflammation in common cardiometabolic disorders suggests the existence of shared pathways between these processes and spondyloarthritis pathophysiology. Thus, a bidirectional relationship exists between the effects of biologic drugs and patients’ cardiometabolic profile, which must be considered during treatment decision making. Biologic therapy may induce changes in patients’ cardiometabolic status and cardiometabolic conditions may conversely impact the clinical response to biologic therapy. Available evidence regarding the impact of IL-17 blockade with secukinumab on cardiometabolic parameters suggests this drug does not interfere with traditional cardiovascular risk markers and could be associated with a decreased risk of cardiovascular events. Additionally, the efficacy and retention rates of secukinumab do not appear to be negatively affected by obesity, with some studies reporting a positive impact on clinical outcomes, contrary to that described with other approaches, such as tumor necrosis factor blockade.. In this article, we also review evidence for this bidirectional association with other treatments for spondyloarthritis. Current evidence suggests that IL-17–targeted therapy with secukinumab is highly effective in spondyloarthritis patients with cardiometabolic comorbidities and may provide additional cardiometabolic benefits.